La Relación entre Actitudes y Conductas Violentas en las Relaciones Interpersonales Íntimas (The association between attitudes and violent behaviors at private and interpersonal relationships) - Alicia Puente; Silvia Ubillos; Darío Páez (Oñati Socio-Legal Series)
The aim of this study is to evaluate the association between attitudes and violent behaviors at private and interpersonal relationships, as well as gender and age differences and the exposure to violent events. It is analyzed the relation between the perpetrated and suffered violence, the health condition, the perception of the social environment and its relation with the cultural values. The sample is based on 2006 persons, 825 men (41.1%) and 1181 women (58.9%). A probabilistic sampling stratified across the cities (Alava, Guipuzkoa y Vizcaya) is developed, according to proportionality criteria during the period 2005-2008. A connection between sharing attitudes and developing violent behaviors was detected. In general, the common violence in the couple is bidirectional and reciprocal, although there are differences between men and women related to severity. The aggression will be associated with violence in childhood, the age and the exposure to violent events. It is verified that violence severely impacts on the physical and mental health of victims and aggressors and it is related to a worse social climate and male cultural values.